1998
DOI: 10.1046/j.1365-2567.1998.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Splenic B cells are required for tolerogenic antigen presentation in the induction of anterior chamber‐associated immune deviation (ACAID)

Abstract: Ocular immune privilege is the result of a number of protective mechanisms, including a specialized immune response to antigen encountered in the anterior chamber of the eye. Anterior chamber-associated immune deviation, or ACAID, is characterized by the antigen-specific, selective down-regulation of systemic cell-mediated and humoral immune responses. One current hypothesis of the initiation of ACAID predicts that ocular APC process antigen and then migrate out of the eye and to the spleen where various regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 34 publications
2
83
0
1
Order By: Relevance
“…Based on these findings, we hypothesized that B cells generate ACAID by presenting antigenic peptides to T cells in the context of Qa-1. Previous studies had shown that ACAID is abrogated in B cell knockout mice and that reconstitution with normal, syngeneic B cells restores ACAID (9). Our hy of the eye with 100 g OVA.…”
Section: The Role Of Nonclassical Class I Molecules In Acaidmentioning
confidence: 63%
See 4 more Smart Citations
“…Based on these findings, we hypothesized that B cells generate ACAID by presenting antigenic peptides to T cells in the context of Qa-1. Previous studies had shown that ACAID is abrogated in B cell knockout mice and that reconstitution with normal, syngeneic B cells restores ACAID (9). Our hy of the eye with 100 g OVA.…”
Section: The Role Of Nonclassical Class I Molecules In Acaidmentioning
confidence: 63%
“…into B celldeficient mice. This procedure was shown to effectively reconstitute B cell knockout mice (9).…”
Section: Reconstitution Of B Cell-deficient Micementioning
confidence: 99%
See 3 more Smart Citations